2014
DOI: 10.1016/j.celrep.2014.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Dnase2a Deficiency Uncovers Lysosomal Clearance of Damaged Nuclear DNA via Autophagy

Abstract: Summary Deficiencies in DNA degrading nucleases lead to accumulation of self DNA and induction of autoimmunity in mice and in monogenic and polygenic human diseases. However, the sources of DNA and the mechanisms that trigger immunity remain unclear. We analyzed mice deficient for the lysosomal nuclease, Dnase2a, and observed elevated levels of undegraded DNA in both phagocytic and non-phagocytic cells. In non-phagocytic cells, the excess DNA originated from damaged DNA in the nucleus based on co-localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
143
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(165 citation statements)
references
References 68 publications
(86 reference statements)
11
143
0
Order By: Relevance
“…Further mechanistic evidence supporting a link between DNA damage and STING-activated IFN pathways was provided by a study demonstrating that DNA damage or defects in the DNA repair system stimulate type I IFN expression in a STING-dependent manner (69). It was also revealed that DNA damage or a failure to repair DNA leads to the accumulation of cellular DNA in the cytoplasm, thus raising the question as to whether the proposed nuclear DNA sensing is in fact the sensing of DNA leaking into the cytoplasm (69)(70)(71). This issue needs further attention and will help clarify the involvement of DNA repair proteins in DNA-driven innate immunity.…”
Section: Interactions Between the Cgas-cgamp-sting Pathway And Othermentioning
confidence: 99%
“…Further mechanistic evidence supporting a link between DNA damage and STING-activated IFN pathways was provided by a study demonstrating that DNA damage or defects in the DNA repair system stimulate type I IFN expression in a STING-dependent manner (69). It was also revealed that DNA damage or a failure to repair DNA leads to the accumulation of cellular DNA in the cytoplasm, thus raising the question as to whether the proposed nuclear DNA sensing is in fact the sensing of DNA leaking into the cytoplasm (69)(70)(71). This issue needs further attention and will help clarify the involvement of DNA repair proteins in DNA-driven innate immunity.…”
Section: Interactions Between the Cgas-cgamp-sting Pathway And Othermentioning
confidence: 99%
“…Two recent studies showed that damaged gDNA fragments are constitutively exported to lysosomes for degradation (Ivanov et al, 2013;Lan et al, 2014). Lack of co-localization of cytosolic 8OHdG(+) DNA and damaged (γ.H2A.X) or fragmented (TUN EL) gDNA markers rules out its nuclear origin (Fig.…”
Section: Res Ultsmentioning
confidence: 99%
“…Interestingly, DNA damage by irradiation or chemicals such as etoposide or cytosine arabinoside (Ara-C), is linked to type I IFN signaling (24)(25)(26). These DNA damaging agents lead to accumulation of cytosolic DNA and activate the IRF3 pathway.…”
mentioning
confidence: 99%